Social Evolution With Decoupling of Multiple Roles of Biogenic Amines Into Different Phenotypes in Hymenoptera - Sasaki, Ken; Okada, Yasukazu; Shimoji, Hiroyuki; Aonuma, Hitoshi; Miura, Toru; Tsuji, Kazuki (Frontiers in Ecology and Evolution, 2021)
Convergent evolution of eusociality with the division of reproduction and its plastic transition in Hymenoptera has long attracted the attention of researchers. To explain the evolutionary scenario of the reproductive division of labor, several hypotheses had been proposed. Among these, we focus on the most basic concepts, i.e., the ovarian ground plan hypothesis (OGPH) and the split-function hypothesis (SFH). The OGPH assumes the physiological decoupling of ovarian cycles and behavior into reproductive and non-reproductive individuals, whereas the SFH assumes that the ancestral reproductive function of juvenile hormone (JH) became split into a dual function. Here, we review recent progress in the understanding of the neurohormonal regulation of reproduction and social behavior in eusocial hymenopterans, with an emphasis on biogenic amines. Biogenic amines are key substances involved in the switching of reproductive physiology and modulation of social behaviors. Dopamine has a pivotal role in the formation of reproductive skew irrespective of the social system, whereas octopamine and serotonin contribute largely to non-reproductive social behaviors. These decoupling roles of biogenic amines are seen in the life cycle of a single female in a solitary species, supporting OGPH. JH promotes reproduction with dopamine function in primitively eusocial species, whereas it regulates non-reproductive social behaviors with octopamine function in advanced eusocial species. The signal transduction networks between JH and the biogenic amines have been rewired in advanced eusocial species, which could regulate reproduction in response to various social stimuli independently of JH action.